Algebraic active disturbance rejection to control a generalized uncertain second-order flat system - Aguilar-Ibanez, Carlos; Suarez-Castanon, Miguel S.; Saldivar, Belem; Jimenez-Lizarraga, Manuel A.; Jesus Rubio, Jose de; Mendoza-Mendoza, Julio (Zielona Góra: Uniwersytet Zielonogórski)
We introduce an algebraically active disturbance rejection-based control solution for the trajectory tracking problem of an uncertain second-order flat system with unknown external disturbances. To this end, we first algebraically identify the system`s unknown dynamics and the external disturbances with a linear set of time-varying integral expressions for the output and the control signal.
Keywords: active disturbance rejection control; uncertain flat system; numerical methods; algebraic estimation; 2-DOF manipulator